2013
DOI: 10.1371/journal.pone.0063800
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Contractile Properties of Myometrium from Singleton and Twin Pregnancies

Abstract: ObjectiveOver half of twin pregnancies in US and UK deliver prematurely but the reasons for this are unclear. The contractility of myometrium from twin pregnancies has not been directly investigated. The objective of this research was to determine if there are differences in the contractile activity and response to oxytocin, between myometrium from singleton and twin pregnancies, across a range of gestational ages. Furthermore, we wished to determine if contractile activity correlates with increasing level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 38 publications
6
33
1
2
Order By: Relevance
“…Increased or aberrant uterine distension may also help explain the high rates of preterm labour often associated with cases of polyhydramnios and multiple pregnancy , particularly if the uterus is subjected to higher degree of stretch at an earlier time point in gestation. Interestingly, our recent in vitro studies of myometrial contraction from twin pregnancies showed an increased response to oxytocin compared to singleton pregnancies , although OTR expression was not examined. The stimulus for the increased OTR expression that is found in preterm labours where they are not confounded by a large foetus or multiple pregnancy (i.e.…”
Section: Regulation Of Myometrial Oxytocin and Otrsmentioning
confidence: 99%
“…Increased or aberrant uterine distension may also help explain the high rates of preterm labour often associated with cases of polyhydramnios and multiple pregnancy , particularly if the uterus is subjected to higher degree of stretch at an earlier time point in gestation. Interestingly, our recent in vitro studies of myometrial contraction from twin pregnancies showed an increased response to oxytocin compared to singleton pregnancies , although OTR expression was not examined. The stimulus for the increased OTR expression that is found in preterm labours where they are not confounded by a large foetus or multiple pregnancy (i.e.…”
Section: Regulation Of Myometrial Oxytocin and Otrsmentioning
confidence: 99%
“…We have previously reported (Turton et al . ) that stretch may play role in determining the frequency and duration of contraction, as we found that with increasing uterine distension (from greater neonatal birth weight) contractions were of shorter duration but increased frequency.…”
Section: Environmentmentioning
confidence: 54%
“…) and multiple pregnancy (Turton et al . ). We would also argue that the intellectual drive for research in this area is as compelling as the clinical need.…”
mentioning
confidence: 97%
“…Furthermore, while induction in whom cervical ripening is not required (no PG group) is associated with a lower rate of CS in the case of singleton pregnancies [18, 19], we did not find the same result in twin pregnancies. We postulate that there may be a different mechanism associated with labor and delivery in twins or that the primary higher risk for CS in twins masks this difference [20, 21]. Since CS rate was similar in both groups, we feel this study indicates that all twins in whom induction of labor is indicated should be informed of a significant risk of unplanned CS, regardless of intervention.…”
Section: Discussionmentioning
confidence: 91%